Modeling of Gigabit Passive Optical Networks - Burhan Sert, Ayse; Unverdi, N. Ozlem (IEEE, 2021)
High-speed data transmissions are becoming more popular day by day because of applications such as video players, live coverages, online games and video conferencing over the internet. Optical communication technologies provide a solution to ever increasing user demands by supporting broad band width, reliable and fast data communications. In this study, Fiber to the X, FTTX, based Gigabit Passive Optical Network, GPON, technology which holds an important position among the communication technologies is analyzed by OptiSystem 16.0 simulation software. Effects of data transmission speed and optical fiber length on system performance is evaluated.
Keywords: Communication technologies; optical communications; optical network; optical fiber; FTTX; GPON; Engineering; Telecommunications